2018
DOI: 10.1002/ente.201700916
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Energy Densities of Sulfur Cathodes using Dispersing and Calendering Processes for Lithium–Sulfur Batteries

Abstract: Lithium–sulfur batteries are nearly ready to be commercialized. However, each material composition has specific challenges regarding its adaption to state of the art production lines of lithium‐ion batteries. The influence of the dispersing and calendering process on the battery performance is investigated with an easy‐to‐implement material approach and a solvent‐based process. The slurry is treated by different dispersing intensities using an extruder and a triple roller mill, which leads to increased energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…These results conflict not only with the ones made by the group of Xiao [24] but also with the ones of Gröbmeyer et al [23] However, these results agree with the studies of Kim et al, [26] as well as with the Kwade group. [25] Both used cathodes with comparable electrode densities (0.6-1.1 g cm À3 ) and showed that the compaction of the cathode has a negligible influence on its performance and capacity at moderate C-rates. Kim et al demonstrated an increase in cycling stability by heavily compacting their cathodes (1.7 g cm À3 ) at elevated temperatures.…”
Section: Galvanostatic Cycling Of the Dry-film Cathodes In Dme/ Dol Electrolytementioning
confidence: 98%
See 3 more Smart Citations
“…These results conflict not only with the ones made by the group of Xiao [24] but also with the ones of Gröbmeyer et al [23] However, these results agree with the studies of Kim et al, [26] as well as with the Kwade group. [25] Both used cathodes with comparable electrode densities (0.6-1.1 g cm À3 ) and showed that the compaction of the cathode has a negligible influence on its performance and capacity at moderate C-rates. Kim et al demonstrated an increase in cycling stability by heavily compacting their cathodes (1.7 g cm À3 ) at elevated temperatures.…”
Section: Galvanostatic Cycling Of the Dry-film Cathodes In Dme/ Dol Electrolytementioning
confidence: 98%
“…This in accordance to the results of Titscher et al, who demonstrated that macropores are eliminated by calendering. [25] In the SEM images with the highest magnification (Figure 1c,f ), the single carbon nanoparticles and the multi-walled carbon nanotubes (MWCNTs) can be observed.…”
Section: Surface Morphology S/c Dry-film Cathodesmentioning
confidence: 98%
See 2 more Smart Citations
“…Foreground data models refer to the processes related to the system under consideration concerning its whole life cycle (i.e., repositories of experimental results from measurements, simulations, calculations, or reports regarding materials, components or processes, industry-specific data, or company internal data). Looking into batteries, considering the different processes for the production lines (e.g., processing electrodes: dispersing, formulation, coating, drying, and calendaring), the process strategies and parameters can strongly influence the energy density of the cathode and the performance of the battery, as investigated for the case of sulfur batteries [15]. In this way, in order to model the foreground processes related to the battery technology involved, understanding the interactions between battery cell production technologies, material and process parameters, and product properties are necessary.…”
Section: Data Modelsmentioning
confidence: 99%